2014
DOI: 10.1007/s13296-014-1220-0
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of single-layer lattice shells with VF-FPB

Abstract: Friction pendulum bearings (FPB) are recognized as a kind of effective isolation device for protecting and retrofitting an existing structure, but they are not adaptive to different seismic inputs due to the constant friction coefficient and constant radius of curvature. A new isolation bearing called variable-friction friction pendulum bearings (VF-FPB) was proposed which could overcome this limitation while retaining all the advantages of an FPB. Unlike a conventional FPB, the sliding surface of a VF-FPB was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For smallφ 1 , the loops follow Eq. (25). For largē ϕ 1 , the loops change with the instantaneous amplitude of the TMD strokes: for small amplitudes (in the first instants of the transient), the loops follow Eq.…”
Section: Actual Vfp-tmdmentioning
confidence: 94%
See 1 more Smart Citation
“…For smallφ 1 , the loops follow Eq. (25). For largē ϕ 1 , the loops change with the instantaneous amplitude of the TMD strokes: for small amplitudes (in the first instants of the transient), the loops follow Eq.…”
Section: Actual Vfp-tmdmentioning
confidence: 94%
“…A similar arrangement has been recently adopted to realize "adaptive" seismic isolators, although several concentric regions are in that case generally admitted. VFP isolators have been postulated in [24], proposed in [25][26][27], and later analyzed by several authors (e.g., [28,29]). They are meant to outperform conventional friction pendulum bearings [30] by undergoing desired stiffness and damping modifications at specified displacement amplitudes, so that the isolation system can be optimized for multiple performance objectives [31].…”
Section: Introductionmentioning
confidence: 99%
“…The research work has demonstrated that horizontal isolation bearings, like rubber bearings and friction pendulum systems, can effectively mitigate earthquake damage. [2][3][4][5][6] As the large-span spatial structure has the characteristics of dense vibration modes, it is more sensitive to seismic effects, especially the vertical component of the ground motions. 4 The vertical ground motion is transmitted unchanged through or even magnified by the isolation system.…”
Section: Noveltymentioning
confidence: 99%
“…Single-layer domes are adopted worldwidely as long-span roofs in recent decades [1][2][3] because of their advantages, such as their good aesthetic appearance, large space coverage capability and sound structural performance. Current research work is mainly focused on the structural response [4][5][6][7][8][9][10], collapse [11][12][13] of the steel structure under different loads through experiment and numerical simulation analysis [14][15][16][17][18], considering stability and buckling [19][20][21][22]. Only few reports have investigated the structural dynamic failure modes [17,19,23,24] and the seismic failure loads when the single-layer reticulated shells are subject to earthquakes.…”
Section: Introductionmentioning
confidence: 99%